Data sources on landscape structure in a highly industrialized area - Mazurek, Kinga (Environmental & socio-economic studies, 2015)
Landscape may be described as a part of space characterized by a certain physiognomy, which is a dynamic system subject to evolution. An important factor influencing the type and condition of the landscape is human activity which shapes or rebuilds its structure. Interesting results may be obtained on comparison of archival cartographic materials with contemporary studies and zoning plans. The Upper Silesian Coal Basin is a region with a clearly transformed landscape. The determinant of the geographical environment transformation here is the anthropogenic factor. The study area includes the upper part of the Kłodnica catchment (229.6 sq km). The study is a review, and its aim is to systematize data sources used in the research on the transformation of landscape structure of a heavily industrialized area. In the first half of the nineteenth century created the "Urmesstischblätter" in the scale of 1:25 000. Afterwards preparations began to take new topographic images of the country (the "Messtischblätter"). In the 1990s initiated the development of a new topographic map (in the scale of 1:10 000). Recent data source is for example the project CORINE Land Cover 2006. There are many of various sources of data on land cover. An important aspect is the proper selection of documents and maps, and their proper interpretation.